Post-Apartheid Legislative Recognition of Traditional Leaders in South Africa: Weak Legal Pluralism in the Guise of Deep Legal Pluralism An analysis and critique of the legislative framework for the recognition of traditional leadership in South Africa under the 1996 Constitution - Mutloane, Mphati Ntebaleng (Department of Public Law, 2015)
This study explores the limitations of recognising traditional leadership as institution through legislation. The legislative recognition of traditional leadership has serious implications for the processes of change within customary law from 'official' customary law to 'living' customary law. The advent of the 1996 Constitution and its emphasis on freedom, dignity, equality and accountability has opened up avenues for democratic political participation, which is changing the nature of customary law through a bottom-up process involving community members in the evolution of customary law. This process of evolution draws on various sources of law, including aspects of official customary law, community norms and procedures as well as the Constitution, particularly rights discourse. Deep legal pluralism has taken root through living customary law and is changing the way in which community members relate to traditional leaders by empowering rural citizens to demand accountability from traditional leaders. Legislative recognition of traditional leadership has been characterised as necessary for the restoration of the dignity of African justice systems. Though constitutionally sanctioned through the rule of law, the legislative framework recognising and regulating traditional leaders has had a negative impact on the processes of change and democratisation described above at grassroots level. Gaining an understanding of these consequences and how they have come about is at the heart of this study, especially given that they are unintended consequences of a government policy meant to improve the lives of rural citizens. Legal pluralism as a theory of law provides a critical lens through which the shortcomings of legislation recognising traditional leadership can be perceived, and probing questions can be asked about the effect of state law on non-state legal orders. However, in South Africa the situation is quite complicated given that the distinction between state law and non-state law with regard to African customary law is not always easy to make. The two systems have existed not only in juxtaposition for many years, but have bled into each other in layered ways. These layers have been moulded very deeply through the influence of various politicolegal orders in existence at particular times and their impact on social relations in South African society. As a theory of law, legal pluralism is used in this study to try and peel back a few of these layers, enabling observation and analysis of how the distribution of political power from the different politico-legal frameworks of governance in South Africa namely, colonialism, apartheid, and constitutional democracy, have shaped traditional leadership; and the impact of these processes on the power relationships between traditional leaders and rural citizens. Law, mostly in the form of legislation, has been an important factor in the establishment, destruction, and re-establishment of these power relationships. This forms the basis of the study, at the end of which it is determined that although legislation is necessary for the recognition and regulation of traditional leadership, as a requirement of the rule of law, the current and proposed legislative framework for traditional leadership is an inappropriate framework. It centralises legislative, judicial and executive power in an unelected arm of government, namely traditional leaders, which is unconstitutional on the basis of the separation of powers principle which is a founding value of South Africa's constitutional democratic dispensation.